Some results on a viscosity splitting algorithm in Hilbert spaces - Zhang, Yunpeng (Journal of inequalities and applications, 2015)
In this paper, a viscosity splitting for common solution problems is proposed.Strong convergence theorems are obtained in the framework of Hilbert spaces.Applications are also provided to support the main results.